Management and diversity : thematic approaches - Chanlat, Jean-Franc<U+00cc>ʹois, 1950-; O<U+00cc>¡zbilgin, Mustafa, (International perspectives on equality, diversity and inclusion ;, 2017)
International Perspectives on Equality, Diversity and Inclusion examines the complex nature of equality, diversity and inclusion in the world of work through interdisciplinary, comparative and critical perspectives. Authors are encouraged to provide cross-national and multi-dimensional insights through comparative analysis and to bring insights from across the disciplines of social sciences and humanities. The series elicits critical scholarship through its focus on structures of inequality in relations of power in exploring issues of EDI at work.